RIFM fragrance ingredient safety assessment, 1-methyl-3-methoxy-4-isopropylbenzene, CAS Registry Number 1076-56-8. (December 2017) - Api, A.M.; Belsito, D.; Botelho, D.; Browne, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; et al.
Highlights: 1-Methyl-3-methoxy-4-isopropylbenzene safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read across and/or TTC.